Teaching identity matching of braille characters to beginning braille readers. Issue 2 (23rd March 2017) - Toussaint, Karen A.; Scheithauer, Mindy C.; Tiger, Jeffrey H.; Saunders, Kathryn J.
Abstract : We taught three children with visual impairments to make tactile discriminations of the braille alphabet within a matching‐to‐sample format. That is, we presented participants with a braille character as a sample stimulus, and they selected the matching stimulus from a three‐comparison array. In order to minimize participant errors, we initially arranged braille characters into training sets in which there was a maximum difference in the number of dots comprising the target and nontarget comparison stimuli. As participants mastered these discriminations, we increased the similarity between target and nontarget comparisons (i.e., an approximation of stimulus fading). All three participants' accuracy systematically increased following the introduction of this identity‐matching procedure.